2002
DOI: 10.1002/1521-3773(20021104)41:21<4085::aid-anie4085>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis of Tetranuclear Ruthenium Polyhydride Clusters and Their Mixed-Ligand Analogues

Abstract: The reactivity of transition-metal cluster complexes has recently been attracted considerable attention because of their potential applicability to organic synthesis. [1] There have been a number of examples of unique reaction modes, such as successive cleavage of the carbon±hydrogen bond of alkanes, [2] the cleavage of the carbon±carbon double bond of 1,1'-disubstituted alkenes, [3] and the catalytic hydrogenation of aromatic compounds in aqueous media, [4] originating from the cooperative action of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 3 publications
3
16
0
Order By: Relevance
“…Analogous structures were reported for other silver compounds. 28,31 Even a tridentate hydrogen is obtained in Ag 6 (H 2 O) 3 H 6 , analogous μ3-H were observed previously. 32 In all the clusters discussed above Ag−Ag bonds are formed.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Analogous structures were reported for other silver compounds. 28,31 Even a tridentate hydrogen is obtained in Ag 6 (H 2 O) 3 H 6 , analogous μ3-H were observed previously. 32 In all the clusters discussed above Ag−Ag bonds are formed.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…The results are in good agreement with other Ag–Ag bond lengths. In the cyclic structures there are bidentate hydrogens. Analogous structures were reported for other silver compounds. , Even a tridentate hydrogen is obtained in Ag 6 (H 2 O) 3 H 6 , analogous μ3-H were observed previously . In all the clusters discussed above Ag–Ag bonds are formed.…”
Section: Resultssupporting
confidence: 81%
“…52 The neo-menthyl cyclopentadienyl (L) complex [RuL(Me)(CO)PPh 3 ] undergoes Ru-Me bond cleavage with retention of configuration using hydrogen halides, but the slower reaction with halogens allowed an intermediate to isomerise. 53 Studies of complexes derived from the 16-electron cation [Ru(Cp)ClL 2 ] (L = phosphine) resulted in the isolation and structural characterization of 55 An unusual stable Ru(0) aqua complex has been isolated using dimethylfumarate (MeO 2 CCH᎐ ᎐ CHCO 2 Me, L) as alkene ligand. [Ru(η 6 -cot)L] reacts with dppe in C 2 H 4 Cl 2 to give the known complexes [Ru(dppe) 2 L] and [Ru(dppe)L 2 ], but also as major product [Ru(dppe)L 2 (H 2 O)], in which the coordinated water is stabilised by hydrogen bonding with the ester carbonyl groups.…”
Section: Ruthenium Organometallic Chemistrymentioning
confidence: 99%
“…Ligand migration involving triorganophosphine (PR 3 ) ligands has sometimes been invoked in the fluxional behaviour of organometallic compounds [1][2][3]. However, there are very few examples in the literature in which activation parameters and standard free energy values for PR 3 migration are available.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are very few examples in the literature in which activation parameters and standard free energy values for PR 3 migration are available. To our knowledge, only two examples have been reported; these are: (i) a series of diruthenium dihydrido complexes, [Cp*Ru] 2 (PR 3 )(l-H) 2 (R = Me, Et, i-Pr, Cy, Bz, OMe, OPh), in which the PR 3 ligand migrated between the two Ru centres (no new isomer was produced) [2], and (ii) the heterometallic clusters PtRu 5 (CO) 16 (l 6 -C)(PMe 2 Ph) and PtRu 5 (CO) 16 (l 6 -C)(PMe 3 ), in which the phosphine ligand migrated between the Pt (major isomer) and the Ru (minor isomer) vertices of an octahedron, with a concomitant CO shift [3]. We have recently reported that the heteronuclear cluster RuOs 3 (l-H) 2 (CO) 13 (1) undergoes facile substitution with PPh 3 under trimethylamine N-oxide activation, to afford the mono-and disubstituted derivatives RuOs 3 (l-H) 2 (CO) 13Àn (PPh 3 ) n (n = 1 (2a) or 2 (3a)).…”
Section: Introductionmentioning
confidence: 99%